IMPACT OF POLY-LINGUISTIC LOAD ON AIR TRAFFIC CONTROL AND MONITORING QUALITY - Kharchenko, Volodymyr; Chepizhenko, Valery; Zaitsev, Yuriy (Proceedings of National Aviation University (archive), 2012)
We have defined the structure and basic characteristics of the poly-linguistic audio-acoustic channel within the framework of controller – pilot communication, and set limits of poly-linguistic load impact on air traffic control.